(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2022)
Bapsi Sidhwa’s book, Ice-Candy-Man, through the eyes of a young narrator from the Parsi diaspora in colonial Lahore, Pakistan, who is a kid of the diaspora, According to Bapsi Sidhwa’s account, the high concept of nationalism was traded for communal thinking during Partition, resulting in tremendous damage as well as political absurdity and a deterioration of social sensitivities. On top of criticising both the British and Indian histories of the subcontinent, Bapsi Sidhwa has also given an alternative history based on Pakistan’s predominant viewpoint. One aspect that will be looked at is how fundamentalism stoked by communal animosity leads to the inevitable logic of partition. The apocalyptic catastrophe is presented via the lens of Parsi sensibility in this book.